Study of Hanoi and HoChiMinh Stock Exchange by Econophysics Methods - Anh, Chu Thuy; Lien, Dao Hong; Lan, Nguyen Tri; Viet, Nguyen Ai (Communications in Physics, 2014)
The econophysics methods are used to study the financial fluctuation of Hanoi Stock Exchange (HNX) and Hochiminh Stock Exchange (HSX) in comparison to Dow John Industrial Average's one. The study has been made both on panic period (2007-2008) and on normal time of theses stocks. The results point out that for the period under consideration, the distribution of returns tends to be Student distribution. There exists an analogy between non-equilibrium phase transitions and financial market movement. Thus it is hypothesized that financial markets undergo self-organizing when the external volatility perception rises above some critical value, the distribution of signs of returns is to be similar to a second order phase transition. The results obtained by econophysics method have quite good agreement with the ones obtained by other economy analyzation methods.